An Exploratory Study of the Effect of Mobile Money Services on the Growth of Micro-Small and Medium-Sized Enterprises in Bosaso: Effect of Mobile Money Services on the Growth of Micro-Small and Medium-Sized Enterprises - malenge, Ezekiel (Dinasti International Journal of Economics, Finance & Accounting, 2022)
The purpose of this exploratory study is to seek information on the effect of Mobile Money Services (MMS) dynamics on the growth of Micro-Small and Medium-sized Enterprises. (MSMEs) The available studies provide limited information on the subject, regarding the growth of micro-small and medium-sized enterprises, especially in Bosaso municipality, Puntland Somalia. The study is guided by the Unified Theory of Acceptance and Use of Technology (UTAUT) to arrive at some of the factors affecting the growth of micro small and medium-sized enterprises. The study is based on a case study carried out using quasi-structured interviews, observation and documentation. The data was collected from a sample of 34 participants. The information gathered indicated that usefulness, social influence, accessibility, cost, enabling environment and trust aspects were linked to behavioural intention to utilise mobile money service, which has the potential to lead to the growth of micro-small and medium-sized enterprises. Furthermore, it was learned that though mobile money service technology is new in the market, but the rate at which it is being adopted is on upward trajectory. Moreover, most of the participants possessed smartphones and they were already utilizing them to conduct their business transactions. The article presents information collected through the administration of interviews, observation and documentation. The findings potentially increase awareness of mobile money technology among MSMEs, policymakers, financial institutions, academicians and researchers. Thus, the overall growth of MSMEs.